The role of the tumour suppressor p33ING1b in human neoplasia. Issue 7 (1st July 2003) - Nouman, G S; Anderson, J J; Lunec, J; Angus, B
Abstract : The inhibitor of growth (ING) genes (ING1–4) probably descend from tumour suppressor genes. ING1 was the first to be identified and later isolated using an approach to detect genes whose expression is suppressed in cancer. The others were isolated through homology and similarity searches in human and mouse databases. All members contain a plant homeodomain involved in macromolecule recognition. Apart from the extensively studied ING1, little is known about the number of transcripts encoded by the other members or their gene structure. ING1 encodes several differentially spliced mRNAs, which may produce a family of proteins. The most widely expressed protein isoform is p33 INGb1, which is involved in restriction of cell growth and proliferation, apoptosis, tumour anchorage independent growth, cellular senescence, maintenance of genomic stability, and modulation of cell cycle checkpoints. ING1 gene mutation is uncommon in cancer, although the subcellular localisation of p33 INGb1 may have an effect on its function. The p33 INGb1 cellular compartmental shift from the nucleus to the cytoplasm may cause loss of normal cellular function, and may play a central role in the pathogenesis of several cancers.